THERAPEUTIC EFFECTS OF WHOLE BRAIN RADIOTHERAPY WITH CARBOPLATIN AS RADIATION SENSITIZER IN MANAGEMENT OF BRAIN METASTASIS: Management of Brain Metastasis - Alvi, Dr Zeeshan Ahmed; ., Ahsan Mahmood; ., Usman Ali; ., Shahid Rasul; ., Talha Maqsood; ., Saira Ahmed; ., Saima Ishtiaq; ., Salman Arif (Pakistan Armed Forces Medical Journal, 2013)
Aim: To determine the efficacy of whole brain radiotherapy (WBRT) with carboplatin as radiation sensitizer in metastatic brain disease in our adult population. Study Design: Quasi-experimental study. Place and Duration: Department of Oncology, Combined Military Hospital (CMH), Rawalpindi, Pakistan from July 2011 to September 2012. Patients and Methods: Forty two patients with metastatic brain disease having ECOG performance status (PS) 3 or less with normal hematological and biochemical profile were treated with WBRT with 6MV Photon beam on linear accelerator using parallel opposed lateral beams to a dose of 30 Gys in 10 fractions. Carboplatin was administered in a dose of 150 mg/m2 on day 1 and 6 of WBRT. Improvement in PS and radiological response on CT scan/ MRI brain before and 30 days after the WBRT using response evaluation criteria in solid tumors (RECIST) was evaluated. Results: Out of 42 patients, 38 (90%) showed improvement in PS, 4 (10%) showed either no improvement or worsening of PS (p< 0.001). Seventeen (41%) patients had complete response, 19 (45%) had partial response, 3 (7%) showed stable disease and 3 (7%) had progressive disease. None of the patients showed grade 3/4 toxicity during treatment. Conclusion: WBRT with carboplatin as radiation sensitizer is effective in palliation of patients with metastatic brain disease.